Disclosing the benefits of multi-strain compounds and their health impact mechanisms utilizing intestinal biomimetic technology - Liao, Jiahao; Huang, Jianyu; Li, Xiaoqiong; Kuang, Jian; Li, Jianqiang; Wang, Weiwei; Li, Jinjun (Frontiers in Microbiology, 2025)
The gut microbiota plays a vital function in preserving intestinal homeostasis and general health. This study examined the impacts of a composite probiotic based on an in vitro fermentation system and an organoid interaction research platform to investigate the effects of composite probiotics. 4P, investigating the impact of gut barrier function through the utilization of in vitro and organoid models. Our findings revealed that 4P demonstrated excellent capabilities for producing short-chain fatty acids, modulating intestinal gas metabolism, and regulating oxidative-reduction potential. Furthermore, the individual strains that comprise 4P were selected for subsequent organoid studies based on previous in vitro strain culture experiments. Our results suggest that 4P and its individual strains hold promise for preserving the gut barrier integrity and function, thereby potentially offering therapeutic benefits in the context of intestinal disorders. These findings underscore the importance of exploring the mechanistic actions of composite probiotics in maintaining gut health and preventing diseases.